ANALISIS BEBAN KOGNITIF DAN KEAKTIFAN SISWA DALAM PENGGUNAAN MEDIA PRESENTASI PADA PEMBELAJARAN DI KELAS V SD NEGERI 2 BULA BARAT - Ruslan Efendi Kilkoda; Farida Febriati (STKIP Subang, 2026)
This study aims to analyze students’ cognitive load and learning participation in the use of presentation media in fifth-grade learning activities at SD Negeri 2 Bula Barat. The study employed a qualitative descriptive approach involving one teacher and 24 fifth-grade students as research subjects. Data were collected through observation, interviews, and documentation. The findings revealed that presentation media containing excessive text and animations increased students’ extraneous cognitive load, causing difficulties in understanding the material and reducing classroom participation. In contrast, simple and well-organized presentation slides supported students’ concentration, comprehension, and active involvement during learning activities. These findings support Sweller’s Cognitive Load Theory, which emphasizes that instructional design should align with students’ working memory capacity. Therefore, teachers are encouraged to design effective presentation media to optimize the learning process.